PARTITIONING OF RAINFALL IN EXPERIMENTAL PLANTATIONS OF Eucalyptus urophylla AND Pinus elliottii - Arcova, Francisco Carlos Soriano; Ranzini, Maurício; Cicco, Valdir de (Floresta, 2018)
In a period of 36 months, the partitioning of rainfall was studied in plantations of 30-year-old Eucalyptus urophylla and Pinus elliottii cultivated in flat drainage lysimeters. Gross precipitation was measured with one rain gauge installed in an open area located near the plantations; throughfall was determined by the arithmetic mean of five rain gauges located under the canopy of each species; stemflow was obtained with polyurethane foam collars connected to plastic containers installed on four trees of each species. The mean proportions of throughfall, stemflow and interception in relation to gross rainfall for eucalyptus were 89.0%, 5.4% and 5.6%, respectively, and for pine, they were 79.8%, 1.0 % and 19.2%, respectively. The interannual variation in the percentages of interception for the two species had an amplitude of approximately 6%. There was marked variation in the proportion of stemflow depending on the season for eucalyptus, averaging 8.7% between April and September and 4.6% from October to March. There was a large number of events with negative interception for eucalyptus. One of the likely causes of the negative interception was capture of fog water by the canopy. Linear regressions estimated that rainfall amounts were responsible for approximately 99% and 70% of the variation in throughfall and stemflow, respectively, in the two plantations.